Novel insights and therapeutic approaches in secondary AML - Marconi, Giovanni; Rondoni, Michela; Zannetti, Beatrice Anna; Zacheo, Irene; Nappi, Davide; Mattei, Agnese; Rocchi, Serena; Lanza, Francesco (Frontiers in Oncology, 2024)
Secondary acute myeloid leukemia (sAML) presents as a complex and multifaceted ensamble of disorders, positioning itself as both a challenge and an intriguing frontier within hematologic oncology. Its origins are diverse, stemming from antecedent hematologic conditions, germline predisposing mutations, or the sequelae of cytotoxic therapies, and its development is driven by intricate genetic and epigenetic modifications. This complexity necessitates a diverse array of therapeutic strategies, each meticulously tailored to address the distinctive challenges sAML introduces. Such strategies require a personalized approach, considering the variegated clinical backgrounds of patients and the inherent intricacies of the disease. Allogeneic stem cell transplantation stands as a cornerstone, offering the potential for curative outcomes. This is complemented by the emergence of innovative treatments such as CPX-351, venetoclax, and glasdegib, which have demonstrated promising results in enhancing prognosis. The evolving landscape of sAML treatment underscores the importance of continued research and innovation in the field, aiming not only to improve patient outcomes but also to deepen our understanding of the disease's biological underpinnings, thereby illuminating pathways toward more effective and individualized therapies.